Pengaruh Intervensi Pemerintah dalam Penanganan Covid-19 Terhadap Return Saham - Toyyibah, Ainun; Narsa, Niluh Putu Dian Rosalina Handayani; Romadhon, Fitri (Universitas Negeri Padang, 2024)
Purpose – This research aims to obtain empirical evidence regarding the influence of government intervention in handling Covid-19 on stock returns.Design/methodology/approach – This research was conducted on companies listed on the LQ45 index of the Indonesia Stock Exchange for 2020-2021. The total number of observations was 43 companies obtained using the purposive sampling method. This research is quantitative using multiple linear regression analysis techniques. The dependent variable in this research is stock returns. The independent variable used is government intervention consisting of social restriction policies, prevention and health policies, and economic support. Three control variables are also used, namely company size, profitability (ROA), and leverage (DER).Findings – The research results show that social restriction policies and economic support have a positive effect on stock returns, while prevention and health policies have a negative effect on stock returns.Originality/value – This research is initial research that provides evidence of the influence of government intervention in handling Covid-19 on stock returns in Indonesia by utilizing the OxCORT index.Research limitations/implications – The implication of this research is that investors can anticipate increases and decreases in company share prices by considering several indices related to government intervention. The coverage area used is only limited to Indonesia.